STRATEGI PENGEMBANGAN PRODUK MELALUI PERANCANGAN DESAIN KEMASAN BARU PADA UMKM WARCOK - Israr, Andi Ahmad; Kamariah, Najmi (Politeknik STIA LAN Makassar, 2023)
MSMEs are one of the sectors that make a major contribution to the Indonesian economy both in the form of gross domestic product, employment, and support for the stability of the financial system and the country's economy. Thus, MSME development is a necessary condition for driving Indonesia's economic growth. Warung Coko-Cokko (WARCOK) is one of the SMEs engaged in the food industry. WARCOK SMEs in marketing their products use polypropylene plastic packaging and plastic-coated oil paper. However, the use of this packaging still has some drawbacks, namely not displaying ordering information, difficulty opening the package because it uses staples, and the packaging also cannot hold oily and runny food so it tears more easily and causes leaks. This research aims to provide solutions for the development of new packaging designs for WARCOK MSME products. The method used in this research is descriptive qualitative. A qualitative descriptive approach uses data collection and collection through observation and interviews by asking questions to several parties involved in the research process. The results of this study indicate that the design of new packaging designs at WARCOK SMEs is carried out through five stages of product development, namely the idea creation stage, idea screening, concept development, and product packaging design to the commercialization stage. After going through these stages, the results show that both business owners and consumers are more likely to choose styrofoam packaging made from polystyrene and paper bowl packaging made from environmentally friendly paper as good packaging and suitable for use by WARCOK SMEs. Both types of packaging materials can prevent food leakage, maintain food integrity, and are practical and ergonomic for use by business owners and consumers.